Digital Empowerment in Public Services: Bridging Access Inequality through Community Technology Literacy - Mega Erdawati; Zulkifli Zulkifli; Andi Asrijal (PT. Anagata Sembagi Education, 2026)
Digital transformation in public services has significantly improved efficiency and accessibility; however, it has also created new forms of inequality, particularly among communities with limited digital access and skills. This study aims to examine how community technology literacy mediates the relationship between digital transformation and digital empowerment in reducing access inequality. A quantitative explanatory approach was employed, with data collected through structured questionnaires distributed to citizens using digital public services. The data were analyzed using Structural Equation Modeling (SEM-PLS) to assess both direct and indirect relationships among variables. The findings reveal that digital transformation has a significant positive effect on community technology literacy, which in turn strongly influences digital empowerment. Both community technology literacy and digital empowerment were found to significantly reduce access inequality in public services. Furthermore, the mediation analysis confirms that community technology literacy serves as a key mechanism linking digital transformation to digital empowerment outcomes. These results highlight the importance of integrating technological development with community-based digital literacy initiatives. In conclusion, this study emphasizes that digital empowerment cannot be achieved solely through technological advancement but requires strengthening community capabilities. Therefore, inclusive digital policies that prioritize literacy development are essential to ensure equitable access to public services.